PENGARUH PENERAPAN PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE DAN BUDAYA TRI HITA KARANA TERHADAP KINERJA MANAJERIAL LEMBAGA PERKREDITAN DESA (LPD) PAKRAMAN PADANGSAMBIAN - Ni Made Mery Yandani; I Gusti Ngurah Putra Suryanata (Jurnal Ilmiah Akuntansi & Bisnis, 2019)
The Influence of Implementation of Good Corporate Governance Principles and Tri Hita Karana Value on Managerial Performance of Village Micro Credit (LPD) at Padangsambian. The current study aims to investigate the influence of transparency, accountability, responsibility, independence, fairness, and THK value on LPD financial performance. Saturated sampling technique were used in the current study, and number of sample used were 30. The data were collected using primary data through the method of survey. The current study used classic assumption test and multiple linear regression test as an analysis technique. Generally, it could be stated that if Good Corporate Governance (X1) and The Value of Tri Hita Karana (X2) increase by one unit (one score), it could has a positive influence towards the managerial performance (Y) of LPD Pakraman Padangsambian. This shows that if Good Corporate Governance (X1) and The value of Tri Hita Karana (X2) are increased, then the performance of individual managerial (Y) will increase. Otherwise, if Good Corporate Governance (X1) and the value of Tri Hita Karana (X2) decrease, there will be a decrease in managerial performance (Y). Keywords: Good corporate governance, Tri Hita Karana value, managerial performance